Identifying the Factors that Influence Students’ Academic Performance as a Function of Teaching Qualities in Ahmed Yasawi International Kazakh-Turkish University - Kaldybay, Kainar; Kumarbekuly, Sanat; Sharipkhanova, Anargul; Dautova, Zukhra; Afanasenkova, Irina; Tarlaubay, Maira (Journal of Ecohumanism, 2024)
Improvement the quality of the teachers is crucially important for the nation that strives for the economic prosperity and social stability. Taking into consideration of this point of view, the paper examines the set of qualities of University teachers with regards to the student academic achievement, identify their significance and propose appropriate methods for improvement the quality of teachers in increasing the student achievement. In this chapter, we explore the importance of teachers’ soft skills in establishing fair, friendly and trusting relationships between students and teachers in order to improve academic performance at Ahmed Yasawi University, Kazakhstan. The data was collected using a mixed method from students at Ahmed Yasawi University. The statistical data were collected through a quantitative questionnaire among 361 students. In order to analyze students’ opinions further, ten interviews were conducted. The experience of teacher training at the University of Bath was used in the study to develop recommendations for Ahmed Yasawi University.